EULAR/eumusc.net standards of care for rheumatoid arthritis: cross-sectional analyses of importance, level of implementation and care gaps experienced by patients and rheumatologists across 35 European countries. Issue 11 (1st September 2020) - Meisters, Rachelle; Putrik, Polina; Ramiro, Sofia; Hifinger, Monika; Keszei, Andras P; van Eijk-Hustings, Yvonne; Woolf, Anthony D; Smolen, Josef S; Stamm, Tanja A; Stoffer-Marx, Michaela; Uhlig, Till; Moe, Rikke Helene; et al.
Abstract : Objective: As part of European League against Rheumatism (EULAR)/European Musculoskeletal Conditions Surveillance and Information Network, 20 user-focused standards of care (SoCs) for rheumatoid arthritis (RA) addressing 16 domains of care were developed. This study aimed to explore gaps in implementation of these SoCs across Europe. Methods: Two cross-sectional surveys on the importance, level of and barriers (patients only) to implementation of each SoC (0–10, 10 highest) were designed to be conducted among patients and rheumatologists in 50 European countries. Care gaps were calculated as the difference between the actual and maximum possible score for implementation (ie, 10) multiplied by the care importance score, resulting in care gaps (0–100, maximal gap). Factors associated with the problematic care gaps (ie, gap≥30 and importance≥6 and implementation<6) and strong barriers (≥6) were further analysed in multilevel logistic regression models. Results: Overall, 26 and 31 countries provided data from 1873 patients and 1131 rheumatologists, respectively. 19 out of 20 SoCs were problematic from the perspectives of more than 20% of patients, while this was true for only 10 SoCs for rheumatologists. Rheumatologists in countries with lower gross domestic product and non-European Union countries were more likely to report problematic gaps in 15 of 20 SoCs, while virtually no differences were observed among patients. Lack of relevance of some SoCs (71%) and limited time of professionals (66%) were the most frequent implementation barriers identified by patients. Conclusions: Many problematic gaps were reported across several essential aspects of RA care. More efforts need to be devoted to implementation of EULAR SoCs.